Preadministration of yerba mate (Ilex paraguariensis) helps functional activity and morphology maintenance of MC3T3-E1 osteoblastic cells after in vitro exposition to hydrogen peroxide (2021)
Natural substances with antioxidant effects may benefit prevention and treatment of people with or prone to bone diseases after menopause, such as osteoporosis. This study aimed to evaluate the in vitro effect of preadministration of yerba mate extract (YM) in the metabolism of MC3T3-E1 osteoblasts exposed to hydrogen peroxide (H2O2). The cells (MC3T3-E1) were cultured in 24-well plates with the concentration of 1 μg/mL yerba mate extract dissolved in culture medium throughout the culture period. Four hours before each experiment, 400 μmol/L H2O2 was added per well to simulate oxidative stress. There were evaluated cell adhesion and proliferation, in situ detection of alkaline phosphatase (ALP), mineralized nodules, and immunolocalization of osteocalcin (OCN), bone sialoprotein (BSP) and alkaline phosphatase (ALP) proteins. The results showed that YM preadministration to H2O2 exposition significatively increased cell adhesion after 3 days as well as proliferation and in situ ALP detection after 10 and 7 days respectively, when compared to H2O2 group. Besides, staining of OCN and BSP proteins was less intense and scattered in poor spread cells with cytoskeletal changes in H2O2 group when compared to control and YM H2O2 group. ALP staining was restrained to intracellular regions and similar in all experimental groups. Our results suggest that preadministration of yerba mate extract may prevent deleterious effects in the morphology and functional activity of osteoblasts exposed to H2O2, which could enable the maintenance of extracellular matrix in the presence of oxidative stress.